Architectural solutions and optimization methods to improve the performance of node.js and vue.js applications - Revenchuk, I.; Steshko, V. (ХНУРЕ, 2022)
Software architecture includes a number of important decisions about the organization of a software system, including the choice of structural elements and their interfaces that make up and unite the system into a single whole; the behavior provided by the joint work of these elements; the organization of these structural and behavioral elements into larger subsystems, as well as the architectural style that this organization adheres to. The performance of a web ap plication is an objective measurement and user experience associated with the loading and operation of the program. Performance is about how long a web application takes to load, becomes interactive and responsive, and how smoothly the interaction with content takes place. The architecture and the steps that need to be taken to optimize the program have always been and will be relevant. Any application has its own architecture, but not every application adheres to the rules for building a good architecture, the same applies to optimization. A program with a good architecture is easier to extend and change, as well as to test, configure and understand. As practice shows, people do not like to wait, and even a three-second delay can force a user to close a tab with a slow resource. Therefore, using a number of optimization methods to improve performance will lead to increased usability and will not force the user to leave the resource due to the fact that it is running slowly. Search engines also pay attention to hundreds of parameters when ranking pages in the search. And one of the most important is the speed of data transfer from the server to the client. Архітектура програмного забезпечення містить у собі низку важливих рішень про організацію програмної системи, серед яких, вибір структурних елементів та їх інтерфейсів, що становлять і об›єднують систему в єдине ціле; поведінка, що забезпечується спільною роботою цих елементів; організацію цих структурних та поведінкових елементів у більші підсистеми, а також архітектурний стиль, якого дотримуєть ся ця організація. Продуктивність веб-додатку – це об›єктивні вимірювання та відчуття користувача, пов›язані із завантаженням і роботою програми. Продуктивність – це про те, як довго веб-додаток завантажується, стає інтерактивним та чуйним, про те, як плавно відбувається взаємодія з контентом. Архітектура та кроки, які необхідно зробити для оптимізації додатку, завжди були і будуть актуальними. Будь-який додаток, має свою архітектуру, але далеко не кожен додаток, дотримується правил, щодо побудови гарної архітектури, те саме стосується і оптимізації. Програму з гарною архітектурою легше розширювати та змінювати, а також тестувати, налагоджувати та розуміти.
Keywords: architecture; optimization methods; web system